2021
DOI: 10.1044/2021_jslhr-20-00172
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Informativeness of Single-Word Samples and Connected Speech Samples in Assessing Speech Sound Disorders

Abstract: Purpose Speech-language pathologists (SLPs) are faced with the challenge of quickly and accurately identifying children who present with speech sound disorders (SSD) compared to typically developing (TD) children. The goal of this study was to compare the clinical relevance of two speech sampling methods (single-word vs. connected speech samples) in how sensitive they are in detecting atypical speech sound development in children, and to know whether the information obtained from single-word sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In both studies by Kehoe and colleagues, the two measures of phonological production (phonetic inventory size and PCC) were extracted from spontaneous language samples. The use of a different sampling condition could lead to other results (DuBois & Bernthal, 1978;Morrison & Shriberg, 1992;Yeh & Liu, 2021). Morrison and Shriberg (1992) observed that the contribution of cognitive-linguistic and pragmatic processes is different in a conversational speech sample versus a single-word naming task.…”
Section: Phonological Production Variablesmentioning
confidence: 99%
“…In both studies by Kehoe and colleagues, the two measures of phonological production (phonetic inventory size and PCC) were extracted from spontaneous language samples. The use of a different sampling condition could lead to other results (DuBois & Bernthal, 1978;Morrison & Shriberg, 1992;Yeh & Liu, 2021). Morrison and Shriberg (1992) observed that the contribution of cognitive-linguistic and pragmatic processes is different in a conversational speech sample versus a single-word naming task.…”
Section: Phonological Production Variablesmentioning
confidence: 99%